The development of biomimetic tactile sensor for fine touch - Tam, Bee Ting (2016)
An essential aspect in the field of engineering is surface roughness. The measurement of surface roughness can identify the functionality and usage of a part in an equipment or a production line. The available commercial machines for surface roughness testing are expensive and incur high repair cost, thus the objective of this project is to create a low cost, effective and long-lasting sensor. The ability to differentiate surface roughness increases tremendously over the years due to technological advancements and breakthrough, especially in applications that utilise robots in roughness testing, such as the semiconductor, medical, and automobile industries. Robots use a method called tactile sensing to detect and differentiate patterns, texture and roughness of an item. Studies have shown that the idea of tactile sensing have been adopted into a robotic finger to mimic how a human finger functions. The tactile sensors that are used to emulate the human mechanoreceptors are consisting of the slow adapting (SA) and fast adapting (FA). An artificial finger will be fabricated with piezoresistive sensors to express as the SA mechanoreceptors and the piezoelectrice sensor to express as the FA mechanoreceptors. Texture of vegetable leaves were introduced to investigate whether it help to improve the signal collected by the tactile sensor. The sensors embedded inside the artificial finger are electrically induced when connected into an electric circuit with a power source, thus producing signals when being tested across the surface different samples used for surface roughness testing. The signals collected are recorded and analysed to evaluate on how effective is the artificial finger on surface roughness testing.